2007
DOI: 10.3748/wjg.v13.i11.1680
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of hypoxia inducible factor 1α mRNA is associated with elevated vascular endothelial growth factor expression and excessive angiogenesis and predicts a poor prognosis in gastric carcinoma

Abstract: of HIF-1α and VEGF. The mean survival time and the 5-year survival rate in cases with positive expression HIF-1α and VEGF and MVD value ≥ 41.5/0.72 mm 2 were significantly lower than those with negative expression of HIF-1α and VEGF and MVD value < 41.5/0.72 mm 2 . CONCLUSION:Overexpression of HIF-1α is found in gastric carcinoma. HIF-1α may induce the angiogenesis in gastric carcinoma by upregulating the transcription of VEGF gene, and take part in tumor invasion and metastasis. They can be used as prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 26 publications
2
27
1
3
Order By: Relevance
“…To evaluate the statistically significant difference in the ratio of cancerous EPAS1 mRNA level to histopathologically unchanged tissue EPAS1 mRNA level between the three DNA methylation ranges (0%-1% methylation, 1%-10% methylation, and 10%-100% methylation), the nonparametric Kruskal-Wallis test was used. HIF1A mRNA levels were increased in cancerous compared with noncancerous tissue (8,11,12,33,34). However, other studies reported a constant HIF1A mRNA level in tumor cells and suggested mainly posttranslational regulation of HIF1A expression (35)(36)(37), which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To evaluate the statistically significant difference in the ratio of cancerous EPAS1 mRNA level to histopathologically unchanged tissue EPAS1 mRNA level between the three DNA methylation ranges (0%-1% methylation, 1%-10% methylation, and 10%-100% methylation), the nonparametric Kruskal-Wallis test was used. HIF1A mRNA levels were increased in cancerous compared with noncancerous tissue (8,11,12,33,34). However, other studies reported a constant HIF1A mRNA level in tumor cells and suggested mainly posttranslational regulation of HIF1A expression (35)(36)(37), which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 92%
“…Many articles describe aberrant HIF1a or EPAS1 protein levels and their association with colorectal cancer prognosis (3)(4)(5)(6)(7)(8)(9)(10). However, there are only few articles about the same issues on the HIF1A and EPAS1 mRNA level (8,11,12). Moreover, relatively little is known about transcriptional regulation of HIF1A and EPAS1.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic potential of VEGF immunohistochemical expression has been reported by many literatures (Cheng et al 2010;Wei et al 2009;Li et al 2008;Wang et al 2008;Liu et al 2007;Chen et al 2007;Han et al 2007;Ma et al 2007;Gao et al 2007;Lou et al 2005;Du et al 2003;Song et al 2002;Jiao et al 2005;Tang et al 2008;Yu et al 2003;Shi et al 2003;Feng et al 2002;Kolev et al 2007;Mizokami et al 2006;Urano et al 2006;Aoyagi et al 2005;Koga et al 2004;Kaneko et al 2003;Takahashi et al 2003;Kawabe et al 2002;Kimura et al 2001;Ichikura et al 2001;Kabashima et al 2001;Maehara et al 2000;Saito et al 1999;Tomoda et al 1999;Tanigawa et al 1997;Baba et al 1998;Maeda et al 1998;Lee et al 2009Lee et al , 2010Oh et al 2008;Choi et al 2006;Park et al 2005;Joo et al 2002Joo et al , 2003. And, the most widely studied prognostic factors on VEGF refer to variables including tumor size, location, his...…”
Section: Introductionmentioning
confidence: 96%
“…Particularly, under hypoxic conditions, HIF-1a serves as a transcription factor that targets several genes, including VEGF, and promotes an adaptive angiogenic response to hypoxia [30]. In clinical settings, it has been shown that HIF-1a is associated with tumor prognosis [31][32][33][34][35].…”
Section: Angiogenesismentioning
confidence: 99%